2006
DOI: 10.1111/j.1365-2966.2006.10106.x
|View full text |Cite
|
Sign up to set email alerts
|

Shapley Optical Survey - I. Luminosity functions in the supercluster environment

Abstract: We present the Shapley Optical Survey, a photometric study covering a ∼2-deg 2 region of the Shapley supercluster core at z ∼ 0.05 in two bands (B and R). The galaxy sample is complete to B = 22.5 (>M * + 6, N gal = 16 588) and R = 22.0 (>M * + 7, N gal = 28 008). The galaxy luminosity function (LF) cannot be described by a single Schechter function due to dips apparent at B ∼ 17.5 (M B ∼ −19.3) and R ∼ 17.0 (M R ∼ −19.8) and the clear upturn in the counts for galaxies fainter than B and R ∼ 18 mag. We find, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 64 publications
4
48
0
Order By: Relevance
“…They also showed that the Schechter function does not fit the LF of extremely low luminosity galaxies. In a Shapley Supercluster region Mercurio et al (2006) conclude that the bright end of the Schechter function is not sufficient to fit the data. Yang et al (2008a) also use different analytical expressions of LFs for different populations: a log-normal distribution for first-ranked galaxies, and a modified Schechter function for satellite galaxies.…”
Section: Comparison With Earlier Studiesmentioning
confidence: 89%
See 1 more Smart Citation
“…They also showed that the Schechter function does not fit the LF of extremely low luminosity galaxies. In a Shapley Supercluster region Mercurio et al (2006) conclude that the bright end of the Schechter function is not sufficient to fit the data. Yang et al (2008a) also use different analytical expressions of LFs for different populations: a log-normal distribution for first-ranked galaxies, and a modified Schechter function for satellite galaxies.…”
Section: Comparison With Earlier Studiesmentioning
confidence: 89%
“…Our study does not include very faint galaxies, as, for example, the study of the core region of the Shapley supercluster (Mercurio et al 2006). Thus future work is needed to understand the difference between the faint ends of the LFs in our and Mercurio et al study. One difference between the earlier studies and our work lies in the use of the analytical LFs.…”
Section: Comparison With Earlier Studiesmentioning
confidence: 99%
“…Although the existence of dips in the red-sequence/early-type LFs has been established in many studies (e.g. Secker & Harris 1996;Mercurio et al 2006;Popesso et al 2006; Barkhouse et al 2007), the depth of the dip and the faint-end slope of the LFs are still not well constrained, varying significantly in different studies. We examine this issue more closely in Section 8.1.…”
Section: Our Samplementioning
confidence: 99%
“…A similar double-power law was also used by Vale & Ostriker (2004) to fit the mass-luminosity relation in their subhalo model and by Cooray & Milosavljević (2005) to fit the LF of central galaxies. Since several papers have shown that the Schechter function is not a best fit for the LF (Blanton et al 2005;Mercurio et al 2006;Yang et al 2008;Tempel et al 2009), especially at the bright end, we shall use the double-power law for analytical approximation. Parameters for the LF approximations are given in Table 3.…”
Section: Determining Environmental Densitiesmentioning
confidence: 99%
“…In Tempel et al (2009) A&A 529, A53 (2011) we have found that the global environment has an important role in determining galaxy properties. Some studies have been dedicated only to special regions: e.g., Mercurio et al (2006) investigate the Shapley supercluster. The dependence on the environment has been also studied numerically (Mo et al 2004) and using semi-analytical models (Benson et al 2003;Khochfar et al 2007).…”
Section: Introductionmentioning
confidence: 99%